The Diversity of Hibiscus rosa-sinensis based on Morphological Approach - Agus Slamet (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
The aim of this research was to know the morphological diversity of Hibiscus rosa-sinensis through visual observation. The character of the qualitative and quantitative morphology of Hibiscus was analyzed descriptively. The result showed that there are 15 types of Hibiscus have morphological differences. There are two kinds of leaf shape that is ovatus and deltoideus. While The leaf base is obtusus, rotundatus and truncatus. The leaf apex includes acute and acuminate. All cultivars have a similar leaf margin that is serrate. The leaf colours are variable ranging from green, young green, dark green and variegate (combination between green and white). The flowers have 6 main color variations i.e beige, yellow, red, orange, pink and white. The corolla forms a single petal or a double petal, with two types of corolla uniquely buds and breech. It can be concluded that the cultivar of Hibiscus rosa-sinensis is variable in leaves and flowers.